2019
DOI: 10.1016/j.cmi.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and echocardiographic predictors of embolism in infective endocarditis: systematic review and meta-analysis

Abstract: Given the serious consequences of embolism, surgical evaluation may be considered in patients with these risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 67 publications
(128 reference statements)
3
28
0
3
Order By: Relevance
“…IE is often accompanied by complications [2,3], primarily the systemic embolic events due to migrating endocardial vegetations [14]. In a recent meta-analysis, embolism was significantly higher in intravenous drug users, HIVand chronic liver disease patients, during staphylococcal infections, and with multiple, mobile, or mitral valve vegetations, and when the vegetation size is over 10 mm, or in PVE patients [22]. These parameters were exceedingly common in our cohort with the resultant arterial emboli in 44.4% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…IE is often accompanied by complications [2,3], primarily the systemic embolic events due to migrating endocardial vegetations [14]. In a recent meta-analysis, embolism was significantly higher in intravenous drug users, HIVand chronic liver disease patients, during staphylococcal infections, and with multiple, mobile, or mitral valve vegetations, and when the vegetation size is over 10 mm, or in PVE patients [22]. These parameters were exceedingly common in our cohort with the resultant arterial emboli in 44.4% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of EE was significantly higher in patients exhibiting mobile vegetations. It is not surprising that mobile vegetation can lead to a higher risk of EE, which has been proven by multiple studies over the past several years 18 …”
Section: Predictors For Eementioning
confidence: 94%
“…A meta‐analysis reviewing 23 studies proved that a higher EE risk existed in IE patients with vegetations on the mitral valve versus the aortic valve 18 . Another study noted that vegetations attached to the anterior mitral leaflet were associated with a higher incidence of embolism 19 .…”
Section: Predictors For Eementioning
confidence: 99%
“…Major predictors of embolism in IE are intravenous drug use, Staphylococcus aureus infection, mitral valve vegetation, and vegetation size >10 mm. 5 CAE is a rare, but lethal, complication of IE with high morbidity and mortality. Previous observational studies showed that the incidence rate of CAE in IE was approximately 0.5%.…”
Section: Discussionmentioning
confidence: 99%